2021
DOI: 10.7554/elife.62250
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in polycomb gene regulation disrupt lineage fidelity in intestinal stem cells

Abstract: Tissue homeostasis requires long-term lineage fidelity of somatic stem cells. Whether and how age-related changes in somatic stem cells impact the faithful execution of lineage decisions remains largely unknown. Here, we address this question using genome-wide chromatin accessibility and transcriptome analysis as well as single cell RNA-seq to explore stem cell-intrinsic changes in the aging Drosophila intestine. These studies indicate that in stem cells of old flies, promoters of Polycomb (Pc) target genes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 108 publications
(166 reference statements)
1
20
0
Order By: Relevance
“…Single-cell RNA-seq data has provided additional evidence that EE cells originate through distinct EEPs [11,30]. It was recently suggested that EE priming in progenitor cells is epigenetically regulated by Polycomb complex proteins [31]. The inactivation of Polycomb leads to downregulation of EE genes, which is likely indirect given Polycomb's well-characterized role in transcriptional repression.…”
Section: Ee Fate and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell RNA-seq data has provided additional evidence that EE cells originate through distinct EEPs [11,30]. It was recently suggested that EE priming in progenitor cells is epigenetically regulated by Polycomb complex proteins [31]. The inactivation of Polycomb leads to downregulation of EE genes, which is likely indirect given Polycomb's well-characterized role in transcriptional repression.…”
Section: Ee Fate and Diversitymentioning
confidence: 99%
“…Recent ATAC-seq data suggests that aging leads to mild alteration of chromatin accessibility at promoters enriched for binding motifs of Polycomb interactors. The authors suggest that changes in ISC H3K27me2 levels, catalyzed by the Polycomb Repressive Complex 2 (PRC2), lead to a bias toward EE fate by upregulation of EE-specific gene expression [31]. Further characterization of chromatin states in young and aged stem cells would be required to establish the full extent of epigenetic alterations in ISC and differentiated cells.…”
Section: Nuclear Organization and Epigenetic Regulation During Agingmentioning
confidence: 99%
“…Among the cell types in the intestine, an age-related decline in the regenerative capability of intestinal stem cells (ISCs), which regenerate the gastrointestinal epithelium, significantly perturbs intestinal homeostasis (133). Using the Drosophila intestine as a model to explore stem cell-intrinsic changes during aging, Tauc et al (134) employed bulk genome-wide chromatin accessibility and transcriptome analysis combined with scRNA-seq to find that promoters of Polycomb target genes become differentially accessible in aged ISCs, resulting in increased expression of enteroendocrine cell specification genes and biased differentiation. In a related study, which reported the construction of an enteric neuronal atlas using RAISIN (ribosomes and intact single nucleus) RNA-seq for profiling intact nuclei with ribosome-bound mRNA and MIRACL-seq (mining rare cells sequencing) for label-free enrichment of rare cell types by droplet-based profiling, dysregulation of circadian genes and genes involved in age-related CNS diseases segregated with chronological age in enteric neurons, suggesting its tight correlation with intestinal and extraintestinal diseases (135).…”
Section: The Digestive Systemmentioning
confidence: 99%
“…Although we documented this effect for CD3+ and CD3-cells in the blood and between 5 different organs, this is likely a general phenomenon. This could be explained by the age-related erosion of epigenetic and chromatin landscape 39 which increases the noise in part through cell-to-cell variation in gene expression 95 , loss of lineage fidelity with age, and activation of lineage-inappropriate genes during aging 81,[96][97][98][99] . Reactivation of human endogenous retroviruses during aging could also contribute to this process 100,101 .…”
Section: Image Reveals Heterogeneity Of In Vivo Reprogramming With Os...mentioning
confidence: 99%